2003
DOI: 10.1161/01.res.0000072971.88704.cb
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Necrosis Factor-α Induces Early-Onset Endothelial Adhesivity by Protein Kinase Cζ–Dependent Activation of Intercellular Adhesion Molecule-1

Abstract: We tested the hypothesis that TNF-alpha induces early-onset endothelial adhesivity toward PMN by activating the constitutive endothelial cell surface ICAM-1, the beta2-integrin (CD11/CD18) counter-receptor. Stimulation of human pulmonary artery endothelial cells with TNF-alpha resulted in phosphorylation of ICAM-1 within 1 minute, a response that was sustained up to 15 minutes after TNF-alpha challenge. We observed that TNF-alpha induced 10-fold increase in PMN adhesion to endothelial cells in an ICAM-1-depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
81
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(87 citation statements)
references
References 30 publications
6
81
0
Order By: Relevance
“…This rapid pattern of activation has also been reported in endothelial cells (16). However, we were unable to measure an increase in PKC phosphorylation using phosphoantibodies due to an elevated basal phosphorylation in rat VSMC.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…This rapid pattern of activation has also been reported in endothelial cells (16). However, we were unable to measure an increase in PKC phosphorylation using phosphoantibodies due to an elevated basal phosphorylation in rat VSMC.…”
Section: Discussionsupporting
confidence: 59%
“…PKC is a critical component of mitogenic signaling in many cell types, mediating ANG II-induced activation of ERK in VSMC (22). Moreover, PKC mediates polymorphonuclear neutrophil adhesion and chemotaxis (20) and endothelial adhesion through phosphorylation of intercel-lular adhesion molecule-1 (16). However, the involvement of PKC or PLD in VSMC adhesion or spreading is not known.…”
mentioning
confidence: 99%
“…This peptide inhibits the translocation and function of PKC␣ and PKC␤ in cultured cells (18,19). The inhibitory peptides for PKC, PKC, and PKC are pseudosubstrates, and they specifically inhibit the isoform activity in various cells including ECs (20,21). All of the peptides are myristoylated, which enables them to cross the cell membrane.…”
Section: Treatment Of Ecs With Tnf-␣ and Inhibitors Or Antisense Oligmentioning
confidence: 99%
“…In fact, the loss of PKCz inhibits most of the signs of asthma in this model, including the recruitment of eosinophils in the bronchoalveolar fluid, as well as secretion of Th2 cytokines by activated T cells, strongly suggesting that PKCz can be considered a therapeutic target in asthma. 48 However, it has been shown that PKCz is required for NF-kB activation in response to TNFa in pulmonary artery endothelial cells, 50 a critical parameter in the expression of leukocyte adhesion molecules. Therefore, it could be argued that this function of PKCz in lung-resident cells could also contribute to its role during asthma.…”
Section: Pkcf In Th2 Polarization and Il-4 Signalingmentioning
confidence: 99%